STRONGLY CLEAN ELEMENTS IN A CERTAIN BLOCK MATRIX RING - Nikkhah, Abolfazl; Davvaz, Bijan (Journal of the Indonesian Mathematical Society, 2016)
In this paper, we investigate the concepts of strongly clean, strongly $\pi$-regular and strongly $J_n$-clean related to the ring $A=\begin{pmatrix}R_RM_S\\0S\end{pmatrix}$. Moreover, we give several equivalent conditions such that an element $\alpha\in End(A)$Â  is strongly clean.DOI :Â http://dx.doi.org/10.22342/jims.22.2.259.151-156